2002
DOI: 10.1126/science.1076535
|View full text |Cite
|
Sign up to set email alerts
|

Structural Adaptations in a Membrane Enzyme That Terminates Endocannabinoid Signaling

Abstract: Cellular communication in the nervous system is mediated by chemical messengers that include amino acids, monoamines, peptide hormones, and lipids. An interesting question is how neurons regulate signals that are transmitted by membrane-embedded lipids. Here, we report the 2.8 angstrom crystal structure of the integral membrane protein fatty acid amide hydrolase (FAAH), an enzyme that degrades members of the endocannabinoid class of signaling lipids and terminates their activity. The structure of FAAH complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
597
0
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(631 citation statements)
references
References 26 publications
22
597
0
12
Order By: Relevance
“…This structure shows structural rearrangements in the substrate access channel region with Phe432 flipping into the acyl chain binding (ACB) channel. However, owing to our FAAH in vitro assay in rat brain homogenate, we docked the compounds to the crystal structure of murine FAAH (PDB code 1MT5) [42] with GOLD [43], and the top-ranking pose of the most abundant cluster was visualized for each enantiomer (see Experimental section for details). There is a speculation of a general FAAH binding mode of Nalkylcarbamates before the acylation (carbamoylation) reaction occurs [24,44,45].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This structure shows structural rearrangements in the substrate access channel region with Phe432 flipping into the acyl chain binding (ACB) channel. However, owing to our FAAH in vitro assay in rat brain homogenate, we docked the compounds to the crystal structure of murine FAAH (PDB code 1MT5) [42] with GOLD [43], and the top-ranking pose of the most abundant cluster was visualized for each enantiomer (see Experimental section for details). There is a speculation of a general FAAH binding mode of Nalkylcarbamates before the acylation (carbamoylation) reaction occurs [24,44,45].…”
Section: Resultsmentioning
confidence: 99%
“…In our docking study, the binding of all the enantiomers was indeed in agreement with this mode, and the ligands were positioned in a conformation where the N-cyclohexyl moiety is pointing towards the branching point of the ACB and substrate access channels, and forming van der Waals interactions with Phe194, Phe244, and Ile491. The oxygen of the carbamate carbonyl is accepting hydrogen bond(s) from the backbone N-H groups of the FAAH oxyanion hole residues (Ile238-Ser241) [42], thus giving rise to a conformation where the electropositive acarbon of the ligand is residing next to the nucleophilic hydroxyl of catalytic Ser241. Moreover, the O-aryl part is pointing towards the cytoplasmic access (CA) cavity leading to the intracellular surface of FAAH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elegant site-directed mutagenesis and X-ray diffraction studies have demonstrated that this unusually broad substrate preference is due to a novel catalytic mechanism involving the amino-acid residue lysine 142. This residue may act as a general acid catalyst, favoring the protonation and consequent detachment of reaction products from the enzyme's active site Bracey et al, 2002). Three serine residues that are conserved in all amidase signature enzymes (S241, S217 and S218 in FAAH) also may be essential for enzymatic activity: serine 241 may serve as the enzyme's catalytic nucleophile, while serine 217 and 218 may modulate catalysis through an as-yet-unidentified mechanism .…”
Section: Anandamide Deactivation: Intracellular Hydrolysismentioning
confidence: 99%